Public spending: Does the human capital of Peru's district mayors matter? - Machacuay Meza, Ciro Ivan (2025)
This study sought to evaluate the impact of the labor competencies of municipal governors on the implementation of the state budget allocated to resource allocation projects in district-level municipalities in Peru during the period 2015-2022. Human capital is analyzed through three dimensions: years of formal education, experience in public office and profession of the mayor. A generalized linear mixed model with random effects was applied, using a base of 13,136 observations corresponding to 3,284 mayors from two different administrations in 1,642 districts. The findings reveal that, although the labor competencies of municipal governors in the implementation of the state budget, it is not the only determining factor. Variables such as years of formal education (A_EDUF, coefficient: 0.014094, p<0.001) and the combination of profession with experience in public office (PROF: A_EXFP, coefficient: 0.008131, p<0.001) have a beneficial and significant result. On the contrary, the combination between government performance and complaints or sentences (A_EXFP: DEN_SEN, coefficient: -0.013281, p<0.030920) negatively affects expenditure execution. The study highlights the relevance of mayors' job skills, but also shows that other factors, such as a history of complaints or judgments, can limit their effectiveness in managing public resources. This suggests that budget implementation in resource allocation projects depends on multiple variables, both personal and institutional.